2020
DOI: 10.1007/s00436-020-06833-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and bioinformatics analysis of Fasciola hepatica somatic proteome in different growth phases

Abstract: Fasciola hepatica ( F. hepatica ) is a well-known zoonotic parasite that is crucial for economic and public health worldwide. Quantitative proteomics studies have been performed on proteins expressed by F. hepatica to investigate the differential expression of proteomes in different growth phases. And the screening of several marker proteins for use as early diagnostic antigens is essential. In this study, high-performance liquid chromatography-tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
1
0
1
Order By: Relevance
“…hepatica Cat L protein using the sera of F. hepatica infected or vaccinated cattle in two independent experiments were identified, and these results were confirmed by other studies (35)(36)(37). The study also demonstrated that vaccinated animals with Cat L showed fluke burden reduction with eliciting antibodies (8).…”
Section: Discussionsupporting
confidence: 74%
“…hepatica Cat L protein using the sera of F. hepatica infected or vaccinated cattle in two independent experiments were identified, and these results were confirmed by other studies (35)(36)(37). The study also demonstrated that vaccinated animals with Cat L showed fluke burden reduction with eliciting antibodies (8).…”
Section: Discussionsupporting
confidence: 74%
“…[ 20 ]; Clonorchis sinensis [ 21 , 22 , 23 ]; Schistosoma spp. [ 24 , 25 , 26 ]; and Fasciola hepatica [ 27 , 28 , 29 ]. To obtain transcriptomic insights into the differential expression of the stage-specific gene in N. fowleri , this study used RNA-Seq to analyze the transcriptome of N. fowleri cysts transferred to encystment buffer for 3 days compared with an N. fowleri trophozoite control group.…”
Section: Introductionmentioning
confidence: 99%
“…La fasciolosis es de gran importancia económica en todo el mundo considerada como una amenaza a nivel global para la salud pública, el bienestar animal, productividad agrícola y la seguridad alimentaria [42], causando enormes pérdidas económicas en la agricultura [4,10]. Según su cuadro clínico, puede clasificarse en dos fases: aguda y crónica, actualmente el diagnóstico se realiza durante la fase crónica, sin embargo, la detección temprana permitiría brindar un tratamiento eficaz y oportuno [33].…”
Section: Introductionunclassified